FTO rs1121980 polymorphism contributes to coronary artery disease susceptibility in a Chinese Han population - Xue Min; Yu-Lan Zhou; Yun-Fei Qu; Zhao-Fu Liao; Heng Li; Jie Cheng; Li-Li Liang; Hai-Liang Mo; Zhu-Guo Wu; Xing-Dong Xiong (Lipids in Health and Disease)
Abstract Background The fat mass and obesity-associated protein (FTO) has been showed to be involved in the pathogenesis and progression of coronary artery disease (CAD). However, the effects of FTO variants on CAD risk remain poorly understood. We herein genotyped three SNPs (rs1121980, rs72803657, and rs4783818) in FTO to investigate the influence of FTO polymorphisms on individual susceptibility to CAD. Methods Genotyping for the three SNPs (rs1121980, rs72803657, and rs4783818) was conducted in a cohort of 712 CAD cases with 349 myocardial infarction (MI) cases and 701 control participants, utilizing the polymerase chain reaction-ligation detection reaction (PCR-LDR) technique. The associations of these SNPs with CAD were analyzed using multivariate logistic regression, and the associations with lipid profiles were assessed by the Kruskal-Wallis or Wilcoxon-Mann-Whitney tests. Results The A allele (OR = 1.26, 95% CI = 1.01–1.57, and P = 0.044) and the AA genotype (OR = 3.13, 95% CI = 1.53–6.38, and P = 0.002) of FTO rs1121980 were significantly associated with an elevated risk of CAD. Similarly, the A allele (OR = 1.54, 95% CI = 1.18–2.02, and P = 0.002) and the AA genotype (OR = 5.61, 95% CI = 2.57–12.27, and P < 0.001) of rs1121980 exhibited increased MI risk. This SNP also showed significant associations under recessive genetic models for both CAD and MI (OR = 3.09, 95% CI = 1.52–6.27, P = 0.002 for CAD; OR = 5.40, 95% CI = 2.49–11.71, P < 0.001 for MI). However, the other two SNPs did not show significant associations with CAD or MI risks under any genetic model tested. Stratified analyses indicated a more pronounced association of the A allele with increased CAD/MI risk among younger participants, non-smokers, and non-drinkers. Interestingly, A allele carriers in younger subjects exhibited higher triglyceride (TG) levels and lower high-density lipoprotein cholesterol (HDL-C) levels compared to non-carriers (P < 0.05). Conclusions Our data provides the first evidence that the FTO rs1121980 polymorphism is associated with an increased risk of CAD in the Chinese population. This association is more significant in younger subjects, likely due to the elevated TG levels and reduced HDL-C levels.